IoT based control system for energy saving in workplaces - Muhammad Ikmal Hakim, Zainuddin (2022)
“An interconnected world”, defined by the implementation of comprehensive smart technologies. Because of the rapid advancements in information and communication technology, including the use of Internet of Things (IoT) systems, a new term has emerged. The Internet of Things is a comprehensive network made up of many components that are interconnected with each other. The system, which consists of several modules, sensors, and computers, directly transmits data and performs predefined operations. The COVID-19 pandemic caused chaos in the organization in ways never felt before. Although many individuals across the global economy continue to work remotely, working life will look different as we move to a work -at -home system. A large number of organizations are looking for technologies that allow the Internet of Things to improve the environment more securely and reduce spending costs as companies strive to collect and improve revenue that has been lost by the epidemic. Smart office systems have been integrated in our vision to increase the efficiency of a building or workplace while reducing electricity consumption. So here we have created a better control system in the office that can be done by using microcontroller (ESP32) acting as a controller and regulator of data input from the sensors. Part of our methodology is to produce prototypes of office systems that can control and monitor all electrical appliances especially lighting systems to produce a good and conducive working environment. These results will be determined by individual preferences and sensor information that has been manually configured by the system manufacturer.